Azimuthal separation in nearly back-to-back jet topologies in inclusive 2- and 3-jet events in $${\text {p}} {\text {p}} $$ pp collisions at $$\sqrt{s}=13\,\text {Te}\text {V} $$ s=13Te - A. M. Sirunyan; A. Tumasyan; W. Adam; F. Ambrogi; E. Asilar; T. Bergauer; J. Brandstetter; E. Brondolin; M. Dragicevic; J. Erö; A. Escalante Del Valle; M. Flechl; et al. (European Physical Journal C: Particles and Fields, 2019)
Abstract A measurement for inclusive 2- and 3-jet events of the azimuthal correlation between the two jets with the largest transverse momenta, $$\varDelta φ _{12}$$ Δϕ12 , is presented. The measurement considers events where the two leading jets are nearly collinear (“back-to-back”) in the transverse plane and is performed for several ranges of the leading jet transverse momentum. Proton-proton collision data collected with the CMS experiment at a center-of-mass energy of $$13\,\text {Te}\text {V} $$ 13Te and corresponding to an integrated luminosity of $$35.9{\,\text {fb}^{-1}} $$ 35.9fb-1 are used. Predictions based on calculations using matrix elements at leading-order and next-to-leading-order accuracy in perturbative quantum chromodynamics supplemented with leading-log parton showers and hadronization are generally in agreement with the measurements. Discrepancies between the measurement and theoretical predictions are as large as 15%, mainly in the region $$177^°< \varDelta φ _{12} < 180^° $$ 177∘<Δϕ12<180∘ . The 2- and 3-jet measurements are not simultaneously described by any of models.